Management of a Patient with Metastatic Colorectal Cancer and Liver Metastases - Muhammad Wasif Saif (Case Reports in Oncological Medicine)
Liver metastases are commonly encountered in patients presenting with metastatic colorectal cancer (mCRC); resection is the treatment of choice. A number of systemic treatment options are currently available for such patients, including the use of 5-fluorouracil-based chemotherapies and oxaliplatin (e.g., FOLFOX) in combination with biologic agents that target angiogenesis (e.g., bevacizumab). For patients with progression following first-line treatment, current second-line options include a change in chemotherapy with bevacizumab (for patients who did or did not receive prior bevacizumab) or FOLFIRI in combination with aflibercept, a more recently approved antiangiogenesis therapy. Neurotoxicity is a well-established adverse event of oxaliplatin-based therapy. The current case details an mCRC patient with liver metastases who was treated with a capecitabine and oxaliplatin regimen (XELOX), and experienced two episodes of transient cortical blindness possibly related to oxaliplatin. After disease progression, the patient was switched to a regimen of FOLFIRI and aflibercept and did well on this second-line regimen.